Deceased Donor Uterine Transplantation: Innovation and Adaptation. Issue 4 (October 2016) - Flyckt, Rebecca L.; Farrell, Ruth M.; Perni, Uma C.; Tzakis, Andreas G.; Falcone, Tommaso
Abstract : This commentary endeavors to share our practical experience in developing and implementing the first uterine transplant clinical trial in the United States. Uterine transplant is a promising novel treatment for uterine factor infertility. After reported successful live births after uterine transplant in Sweden, research teams around the world are either embarking on or are considering the development of uterine transplant protocols. Our observations on the applied rather than theoretical aspects of uterine transplantation research in human subjects are detailed in this article. Important among these considerations are composing a broad and experienced multidisciplinary team as well as performing adequate preclinical preparations, including ideally animal studies and practice organ procurements. Ethical preparation is tantamount to clinical preparation for the complexities inherent in uterine transplant, and our suggestions for updating the current ethical criteria for uterine transplant are outlined here. We also describe our perspectives on the strengths and weaknesses of living compared with deceased donor models. Finally, we describe how a strong program can recover and adapt in the face of setbacks to continue a path toward innovation. Abstract : We endeavor to share our practical experience in developing, implementing, and adapting the first uterine transplant clinical trial in the United States.